Phase Ib study of atezolizumab combined with cobimetinib in patients with solid tumors. (27th March 2019) - Hellmann, M D; Kim, T -W; Lee, C B; Goh, B -C; Miller, W H; Oh, D -Y; Jamal, R; Chee, C -E; Chow, L Q M; Gainor, J F; Desai, J; Solomon, B J; et al.
Abstract: Background: Preclinical evidence suggests that MEK inhibition promotes accumulation and survival of intratumoral tumor-specific T cells and can synergize with immune checkpoint inhibition. We investigated the safety and clinical activity of combining a MEK inhibitor, cobimetinib, and a programmed cell death 1 ligand 1 (PD-L1) inhibitor, atezolizumab, in patients with solid tumors. Patients and methods: This phase I/Ib study treated PD-L1/PD-1-naive patients with solid tumors in a dose-escalation stage and then in multiple, indication-specific dose-expansion cohorts. In most patients, cobimetinib was dosed once daily orally for 21 days on, 7 days off. Atezolizumab was dosed at 800 mg intravenously every 2 weeks. The primary objectives were safety and tolerability. Secondary end points included objective response rate, progression-free survival, and overall survival. Results: Between 27 December 2013 and 9 May 2016, 152 patients were enrolled. As of 4 September 2017, 150 patients received ≥1 dose of atezolizumab, including 14 in the dose-escalation cohorts and 136 in the dose-expansion cohorts. Patients had metastatic colorectal cancer (mCRC; n  = 84), melanoma ( n  = 22), non-small-cell lung cancer (NSCLC; n  = 28), and other solid tumors ( n  = 16). The most common all-grade treatment-related adverse events (AEs) were diarrhea (67%), rash (48%), and fatigue (40%), similar to those with single-agent cobimetinib and atezolizumab. One (<1%) treatment-related grade 5 AE occurred (sepsis). Forty-five (30%) and 23 patients (15%) had AEs that led to discontinuation of cobimetinib and atezolizumab, respectively. Confirmed responses were observed in 7 of 84 patients (8%) with mCRC (6 responders were microsatellite low/stable, 1 was microsatellite instable), 9 of 22 patients (41%) with melanoma, and 5 of 28 patients (18%) with NSCLC. Clinical activity was independent of KRAS/BRAF status across diseases. Conclusions: Atezolizumab plus cobimetinib had manageable safety and clinical activity irrespective of KRAS/BRAF status. Although potential synergistic activity was seen in mCRC, this was not confirmed in a subsequent phase III study. ClinicalTrials.gov Identifier: NCT01988896 (the investigators in the NCT01988896 study are listed in the supplementary Appendix, available at Annals of Oncology online).